Hubungan antara Panjang Rantai Amilopektin dan Indeks Glikemik Pangan Karbohidrat: Review - Afandi, Frendy (Food Scientia : Journal of Food Science and Technology, 2023)
The relationship between starch characteristics and the glycemic index (GI) of carbohydrate foods is interesting to study. One of the advances in analytical techniques in characterizing starch is measuring the degree of polymerization of amylopectin chains. Amylopectin is the main component of carbohydrate starch granules. There have been many publications regarding long chain fractions of amylopectin. The aim of this research is to analyze the relationship between amylopectin chain length and the glycemic index of carbohydrate foods. The method used was to tabulate various studies related to data on amylopectin chain length and the glycemic index of carbohydrate foods. Then a regression analysis was carried out between the degree of polymerization of the amylopectin chain and the Pearson correlation between the degree of polymerization and the glycemic index value. The research results showed that there was a strong correlation between the amylopectin chain length with degree of polymerization (DP) 6-12, 13-24, and 25-36 with the glycemic index value of carbohydrate foods. The degree of polymerization of the amylopectin chain is the number of glucose units that make up the chain. The resulting regression equation is y=0.3123x-0.6256 with a value of r2=0.991. The chain length of amylopectin influences starch properties, including the glycemic index. Starches with shorter amylopectin chains have a lower glycemic index, while starches with longer amylopectin chains have a higher glycemic index. The results of this research provide a new perspective for the field of food chemistry that the characteristics of amylopectin influence the glycemic index value of carbohydrate foods.